Photonic Microwave Signal Mixing Using Sagnac-Loop-Based Modulator and Polarization-Dependent Modulation - Beilei Wu; Muguang Wang; Yu Tang; Jian Sun; Shuisheng Jian (IEEE Photonics Journal)
A photonic-assisted microwave mixer using a Sagnac-loop-based modulator and polarization-dependent modulation is proposed and experimentally demonstrated. In this scheme, a dual-parallel Mach–Zehnder modulator (DPMZM) is incorporated in a Sagnac loop, where light is single-sideband (SSB) modulated along one direction with no modulation along the opposite direction due to the traveling-wave velocity mismatch in DPMZM. The SSB-modulated light and unmodulated optical carrier (OC) with opposite propagation directions and orthogonal polarizations are combined via a polarization beam combiner, and thus, a partial orthogonal SSB-modulated signal is obtained, which is then injected into a Mach–Zehnder modulator (MZM) via a polarization controller to ensure the polarization of the unmodulated OC paralleling with the transverse electric (TE) principal axis of MZM. Thus, only the OC is modulated by the data, and the first-order sidebands pass through the MZM directly without modulation based on the polarization dependence of MZM. After a polarizer for polarization interference and a photodetector for optical-to-electrical conversion, a phase-stable microwave signal is obtained. By adjusting the bias point of MZM, clear eye diagrams, and waveforms of 1 Gb/s on-off keying (OOK), amplitude-shift keying (ASK), and binary-phase-shift keying (BPSK) signals at 8 GHz are experimentally achieved.